Application of Factor Analysis for Extracting Significant Factors Related to Futsal - Shrestha, Noora (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2018)
Futsal is becoming an appropriate choice and alternative means of entertainment for the urban people. It can be played in a limited space, for a comparatively shorter time period, and with a small team. The objective of the study was to identify the factors associated with the students’ perception to play the Futsal. The young college students (n = 110) completed a self-administered questionnaire to acquire their perception on the Futsal. The questionnaire was prepared using Likert scale with five options (strongly agree to strongly disagree). The descriptive cross-sectional study used exploratory factor analysis with varimax rotation method to extract the factors related to Futsal. The result revealed that social benefit, health benefit, and the reward were the major three components that had positively influenced majority of the students and their perception on the Futsal game was positive.